Реализация возможности создания локальных копий дистанционных курсов системы «Moodle» - Бордюг, В. Ю. (УАДО, 2004)
The utility for system «Moodle» is viewed below. This software allows to create a local archiving copies of education objects from system «Moodle». These copies don’t contain unnecessary for local copy information. They don’t require some additional analysers. So it’s useful and convenient for users of «Moodle» to receive such local copies for courses they are studying
Keywords: дистанционное обучение